1995
DOI: 10.1111/j.1469-8986.1995.tb03400.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of visual selective attention

Abstract: Visual selective attention improves our perception and performance by modifying sensory input.s at an early stage of processing. Spatial attention produces the most consistent early tnodulations of visual processing, which can be observed when attention is voluntarily allocated to locations. These effects of spatial attention are similar when attention is cued in a trial-by-trial, or sustained, fashion and are manifest as changes in the atnplitudes, but not the latencies, of evoked neural activity recorded fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

71
553
11
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 792 publications
(639 citation statements)
references
References 65 publications
71
553
11
4
Order By: Relevance
“…Amplitude modulations as a function of cueing are also present in visual ERPs beginning , 100 ms after target presentation, with larger amplitudes to valid targets in both younger (Luck, 1995;Mangun, 1995;Mangun and Hillyard, 1991) and older subjects (Curran et al, 2001). Age differences in ERP attention effects have not been studied using auditory cued attention tasks, but have been assessed using dichotic listening tasks.…”
Section: Introductionmentioning
confidence: 92%
“…Amplitude modulations as a function of cueing are also present in visual ERPs beginning , 100 ms after target presentation, with larger amplitudes to valid targets in both younger (Luck, 1995;Mangun, 1995;Mangun and Hillyard, 1991) and older subjects (Curran et al, 2001). Age differences in ERP attention effects have not been studied using auditory cued attention tasks, but have been assessed using dichotic listening tasks.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore the visual N100 has been shown to be functionally independent from other visual evoked potentials, such as the P100 (Spitz et al, 1986;Luck and Hillyard, 1995). Specifically, the P100 typically peaks around 80-130 ms over occipital areas and is sensitive to spatial location in the visual field (Mangun, 1995), luminance (Cant et al, 1978), shape and color (Luck et al, 1995). Differently, the visual N100 has an early anterior (around 140 ms) and a later posterior deflection (temporo-occipital sites around 190 ms) and, although sensitive to low level attributes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Psychophysiological studies measuring visual event-related potentials (VEPs) have shown that focusing the spotlight on a certain location in space leads to an enhancement of early sensory evoked responses as compared to when stimuli were presented outside the beam of the spotlight (e.g. Mangun et al, 1993;Gomez-Gonzales et al, 1994;Mangun, 1995;Anllo-Vento and Hillyard, 1996;Hillyard and AnlloVento, 1998;Luck and Ford, 1998). Moreover, human positron emission tomography (PET) studies have suggested that attending to a particular stimulus enhances cerebral blood¯ow in those cortical areas which are specialized for processing the relevant features of that stimulus (Corbetta et al, 1990;Corbetta et al, 1993;Heinze et al, 1994).…”
Section: Introductionmentioning
confidence: 99%